Candle auctions - Botelho, Tiago Cardoso (2024)
In this dissertation, I develop and solve a model of candle auctions, i.e., dynamic auctions with random termination. In the baseline model, I assume that bidders have independent private values, and that they bid sequentially, one at a time, across two time periods. I show that the second bidder will match the bid of the first bidder whenever it is profitable for him to do so. The first bidder’s optimal bid is given by the difference between his value and a shading factor, depending on the probability that the auction ends before a second round of bidding takes place. I show that although candle auctions may mitigate the issue of late bidding, they do so at the expense of expected revenue.